Flight Control Design for a Tailless Aircraft Using Eigenstructure Assignment - Clara Nieto-Wire; Kenneth Sobel (International Journal of Aerospace Engineering, 2011)
We apply eigenstructure assignment to the design of a flight control system for a wind tunnel model of a tailless aircraft. The aircraft, known as the innovative control effectors (ICEs) aircraft, has unconventional control surfaces plus pitch and yaw thrust vectoring. We linearize the aircraft in straight and level flight at an altitude of 15,000 feet and Mach number 0.4. Then, we separately design flight control systems for the longitudinal and lateral dynamics. We use a control allocation scheme with weights so that the lateral pseudoinputs are yaw and roll moment, and the longitudinal pseudoinput is pitching moment. In contrast to previous eigenstructure assignment designs for the ICE aircraft, we consider the phugoid mode, thrust vectoring, and stability margins. We show how to simultaneously stabilize the phugoid mode, satisfy MIL-F-8785C mode specifications, and satisfy MIL-F-9490D phase and gain margin specifications. We also use a cstar command system that is preferable to earlier pitch-rate command systems. Finally, we present simulation results of the combined longitudinal/lateral flight control system using a full 6DOF nonlinear simulation with approximately 20,000 values for the aerodynamic coefficients. Our simulation includes limiters on actuator deflections, deflection rates, and control system integrators.